Macitentan: entry-into-humans study with a new endothelin receptor antagonist - Sidharta, Patricia N.; van Giersbergen, Paul L. M.; Halabi, Atef; Dingemanse, Jasper (European journal of clinical pharmacology, 2011)
Purpose To study the pharmacokinetics, pharmacodynamics, and tolerability of rising single doses of macitentan, an endothelin receptor antagonist, in healthy male subjects. Methods This double-blind, placebo-controlled study was performed in seven groups of eight healthy male subjects. Doses of 0.2, 1, 5, 25, 100, 300 and 600 mg or placebo (two subjects per group) were administered. Plasma macitentan and endothelin-1 and serum total bile salt concentrations were measured and analysed non-compartmentally. Plasma and urine were analysed qualitatively for the presence of metabolites and one of these, ACT-132577, was also measured quantitatively in plasma. Standard tolerability measurements were performed throughout the study. Results Macitentan was slowly absorbed and, at a dose of 300 mg, the t 1/2 (95% confidence interval, CI) was 17.5 h (14.1, 21.8). The dose-proportionality coefficient β for C max (95% CI) was 0.83 (0.79, 0.87) indicating less than dose-proportional pharmacokinetics of macitentan. In plasma, a pharmacologically active oxidative depropyl metabolite, ACT-132577, was found whereas in urine two minor metabolites were detected. The t 1/2 of ACT-132577 (95% CI) was 65.6 h (53.1, 80.9). Macitentan dose-dependently increased endothelin-1 concentrations up to 2.2-fold (95% CI 1.4, 2.4) at a dose of 600 mg, but had no consistent effect on total bile salts. Macitentan was well tolerated up to and including a dose of 300 mg, the maximum tolerated dose. Headache, nausea and vomiting were dose-limiting adverse events. Conclusion The pharmacokinetic and tolerability profile of macitentan is consistent with a once-a-day dosing regimen and warrants further investigation in clinical studies.